1995
DOI: 10.1113/jphysiol.1995.sp020747
|View full text |Cite
|
Sign up to set email alerts
|

Tachykinins as mediators of slow EPSPs in guinea‐pig gall‐bladder ganglia: involvement of neurokinin‐3 receptors.

Abstract: 1. The effects of endogenous tachykinins and related peptides on intact guinea-pig gallbladder neurones were investigated with single-electrode voltage-and current-clamp recording techniques.2. Pressure ejection of substance P (100 #M) caused a long lasting membrane depolarization that was associated with a decrease in input resistance. In cells that were voltage-clamped to their resting membrane potential, substance P activated an inward current. 3. The reversal potentials of the substance P-induced depolariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…These data suggest that tachykinins might be transmitters at synapses in the ganglia. Consistent with this are pharmacological studies in which a block of NK 1 or NK 3 receptors has antagonised neuro-neuronal transmission in enteric ganglia (Mawe, 1995;Johnson et al, 1998;Frieling et al, 1999;Neunlist et al, 1999). At the light microscope level, NK 1 receptors appear to be evenly distributed over the surfaces of nerve cells.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…These data suggest that tachykinins might be transmitters at synapses in the ganglia. Consistent with this are pharmacological studies in which a block of NK 1 or NK 3 receptors has antagonised neuro-neuronal transmission in enteric ganglia (Mawe, 1995;Johnson et al, 1998;Frieling et al, 1999;Neunlist et al, 1999). At the light microscope level, NK 1 receptors appear to be evenly distributed over the surfaces of nerve cells.…”
supporting
confidence: 61%
“…Previous studies have shown that tachykinin-immunoreactive nerve terminals make appositions with the vast majority of myenteric neurons (Llewellyn-Smith et al, 1984). As many myenteric neurons express NK 3 receptors (Mawe, 1995;Johnson et al, 1998;Frieling et al, 1999;Jenkinson et al, 1999), the distribution of tachykinin-containing nerve terminals is likely to be correlated with the presence of NK 3 receptors, as well as NK 1 receptors, on postsynaptic neurons. It is also likely that tachykinin-containing nerve terminals also form appositions with neurons that express neither NK 1 or NK 3 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The role of substance P as a mediator of the sEPSP has already been shown in the guinea-pig ileum (Katayama & North, 1978) and the NK_3 receptor agonist senktide has been shown to induce sEPSPlike responses in AH neurones (Bertrand & Galligan, 1995). In addition, in myenteric neurones of the duodenum, the stomach, and the gall blader NK_3 receptor agonists were more effective in inducing sEPSP like responses than SP or NK_1 receptor agonists (Hanani et al 1988;Schemann & Kayser, 1991;Mawe, 1995). The inability of the NK_3 antagonist SR 142801 to fully block sEPSPs may have different causes.…”
Section: Pharmacology Of the Sepspmentioning
confidence: 97%
“…However, as N/OFQ is a long (17 aa) peptide and contains several positively charge residues, it is likely that the nerve endings and/or nerve connections between the esophagus and airways in the autonomic ganglia (Myers & Undem, 1993;Myers et al, 1996), where anatomical studies have demonstrated the presence of axon collaterals from visceral afferent fibers (gastrointestinal tract, bladder, airways) (Coleridge et al, 1989;Mawe, 1995;Canning et al, 1996;Myers et al, 1996), represent the site of action of N/OFQ. Interestingly, Canning et al (1998) have reported in an in vitro preparation of guinea-pig trachea and esophagus with their respective nerves that capsaicin elicited a concentrationdependent relaxation of the trachea only when the adjacent esophagus was intact.…”
Section: Discussionmentioning
confidence: 99%